CYP4F2 and CYP3A5 gene polymorphisms and lung cancer in Chinese Han population - He, Ruiqing (Clin Exp Med, 2020)
This study aimed to explore whether the polymorphisms of CYP4F2 and CYP3A5 are correlated with the risk of lung cancer development. A case–control study was conducted among 510 patients with pathologically confirmed lung cancer as the case group and 504 healthy individuals as the control group. Four single-nucleotide polymorphisms of the CYP4F2 and CYP3A5 genes were genotyped, and their correlations with the risk of lung cancer were examined using Chi-square test and logistic regression analysis. Stratified analysis found that the rs3093105 and rs3093106 loci of CYP4F2 gene were significantly associated with lower risk of lung cancer (P = 0.012, OR 0.64, 95% CI 0.45–0.91). The correlation was related to patients’ age and sex and pathological type of lung cancer. Similarly, the rs10242455 loci of CYP3A5 gene showed a statistical significance between the case group and the control group (P = 0.018, OR 0.71, 95% CI 0.53–0.94), which also was associated with reduced risk of squamous cell lung cancer in the dominant and additive models (dominant: OR 0.66, 95% CI 0.46–0.94, P = 0.021; additive: OR 0.71, 95% CI 0.53–0.95, P = 0.023). CYP4F2 and CYP3A5 gene polymorphisms are associated with the reduced risk of non-small cell lung cancer, and its correlation is related to patients’ age and sex and pathological type of lung cancer.